Notarial Risk Mitigation in Entrusted Income Tax Payments under Land Sale and Purchase Binding Agreements - Amanda Putri Rahmawati; Tunggul Anshari Setia Negara; Dyah Widhiawati (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
This study aims to analyze the role of Notaries in the practice of receiving entrusted payments of Final Income Tax in the context of Sale and Purchase Binding Agreements of land and/or buildings, and to formulate a legal risk mitigation model applicable in notarial practice. This research employs a socio-legal method with statutory, conceptual, and futuristic approaches. Data were obtained through interviews with Notaries in Batu City, East Java, Indonesia, as well as through a review of relevant legislation, legal documents, and academic literature. The findings indicate that the practice of Notaries receiving entrusted tax payments has developed as a response to transactional needs and the fiduciary relationship between Notaries and clients, despite the absence of explicit regulation under the Notary Law or Indonesian tax regulations. This normative gap constitutes a legal vacuum that creates legal uncertainty regarding the authority, responsibilities, and limitations of Notaries in managing entrusted tax funds. The study identifies that such practices pose multidimensional legal risks, including civil liability (breach of contract and tort), criminal liability (embezzlement and breach of trust), administrative sanctions within the notarial system, and tax compliance risks. Therefore, a structured risk mitigation framework grounded in the prudential principle is required. The novelty of this research lies in the development of a legal risk mitigation model for Notaries in handling entrusted Final Income Tax payments in Sale and Purchase Binding Agreements transactions. The model encompasses the strengthening of the prudential principle, the implementation of segregated escrow accounts, standardized documentation-based administrative procedures, and the reinforcement of normative regulation concerning the limits of Notaries’ authority in managing entrusted tax funds. This model is expected to enhance legal certainty, provide legal protection for Notaries, and prevent potential misuse of entrusted funds in notarial practice.